How Does Corporate Social Responsibility Affect Financial Performance and Tax Avoidance in ASEAN Companies? - Poppy Dian Indira Kusuma,; Emir Surya Rahmajati,; Eko Suyono,; Icuk Rangga Bawono,; Dona Primasari, (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: This study aims to shed light on the relationship between Corporate Social Responsibility (CSR), financial performance, and tax avoidance among ASEAN-listed companies, while taking into account the role of the Board of Directors (BoD) as a moderating variable. Design/Methodology/Approach: This study adopts a quantitative approach and utilises panel data from 181 publicly listed companies across six ASEAN countries, Indonesia, Thailand, Singapore, Malaysia, Philippines, and Vietnam, covering a ten-year period (2013–2022). Multiple linear regression was employed to examine the direct effect of CSR on financial performance (measured by ROA, ROE, NPM) and tax avoidance (measured by ETR and NETR), as well as the moderating role of the BoD. Robustness tests were performed using alternative model specifications and sub-sample analyses. Research findings: The findings indicate that CSR exerts a positive relationship with financial performance. By contrast, this study fails to prove the ability of CSR to reduce tax avoidance. The moderating role of the BoD exhibits mixed results, demonstrating greater consistency in curbing tax avoidance than in enhancing financial performance. Robustness checks further validate the stability of the main findings. Theoretical Contribution/Originality: This study extends CSR and corporate governance literature by offering cross-country evidence from ASEAN countries, highlighting the varying effectiveness of CSR and the BoD in influencing both financial performance and tax avoidance. Practitioner/Policy implications: Integrating CSR into corporate strategy, when reinforced by competent and responsive boards, has the potential to improve financial performance and reduce tax avoidance, particularly when adapted to country-specific regulatory and cultural contexts. Research Limitations: Among the limitations are those regarding access to the data and language barriers, particularly in Vietnam and Thailand, where annual and sustainability reports are primarily in local languages.